Effect of Xylanase-Assisted Treatment of Oxygen-Delignified Eucalypt Kraft Pulp on ECF Bleaching - Matos, José M.S. (2023)
The effects of treating industrial (laboratory-unwashed) oxygen-delignified eucalypt kraft pulp with a commercial endo-xylanase (X) on ECF bleaching performance were evaluated. Changes in fibre morphology, pulp bleachability and quality, and bleaching effluent parameters were assessed. Although no significant morphological changes were observed, fibres showed some external fibrillation. The X stage reduced both the amount and the integrity of xylans remaining in the fibres, causing their redistribution inside the cell wall. In bleaching, the X treatment allowed the reduction of ClO2 and NaOH loads by 20 and 10%, respectively. Furthermore, the brightness stability of enzyme-treated bleached pulps was improved, which was assigned to the decrease in the content of hexenuronic acid residues. The X treatment did not affect the cellulosic counterpart of pulp and did not cause a significant impact on the papermaking properties, even when xylan degradation was somewhat excessive. The enzymatic treatment caused a significant increase in the chemical oxygen demand (COD) of the respective effluent. The realistic conditions used provide a better insight into the overall impact of this technology at a pulp mill.